Identification and Characterization of Genes Involved in Ecdysteroid Esterification Pathway Contributing to the High 20-Hydroxyecdysone Resistance of Helicoverpa armigera - Duan, Hengtong; Yang, Xin; Bu, Zhanyao; Li, Xinyue; Zhang, Ze; Sun, Wei (Frontiers in Physiology, 2020)
Abstract: 20-hydroxyecdysone (20E), the most important regulator for the insect development, is also the major component of phytoecdysteroids in plants. Therefore, the plant derived hormone was considered as the potential natural products in pest management. However, some insects show high resistance to it, and the molecular mechanism of the resistance is still unclear. In this study, we found that the cotton bollworm Helicoverpa armigera larvae show highly tolerance to artificial foods containing up to 50 μg 20E without any detrimental effects on growth and development. High performance liquid chromatography (HPLC) analysis indicates that high efficiency to transform the ingested 20E through ecdysteroid esterification pathway may contribute to the resistance. Furthermore, comparative transcriptome analysis of larvae midgut after 20E treatment identify the two genes (long-chain-fatty-acid–CoA ligase, Long-FACL; sterol O-acyltransferase, SATF) involved in the pathway. Transcriptome and real-time PCR show Long-FACL gene can be significantly induced by 20E, and this induction is only detected in midgut. However, 20E has no effect on the transcript of SATF gene. Moreover, the heterologously expressed proteins of the SATF gene shows the ecdysteroid-22-O-acyltransferase, and its activity requires fatty acyl-CoA produced by Long-FACL. Taken together, our results identifies and demonstrates the genes involved in ecdysteroid esterification pathway confer high resistance to 20E in the cotton bollworm, Helicoverpa armigera.